Elaboration of distilled beverage from spent coffee ground - Sampaio, A. (2011)
Spent coffee ground (SCG) is the solid residue obtained from the treatment of coffee powder with hot water to prepare instant coffee, and constitutes the main coffee industry residue. Finding alternatives for the reuse of this residue is of great interest from economical and environmental viewpoints. The goal of the present study was to use this residue as raw material for the production of a new distilled beverage. The process for elaboration of this beverage consisted in an initial extraction of the aromatic compounds from SCG with water, followed by the fermentation of this extract in a bench bioreactor and subsequently distillation of the fermented broth. The produced drink contained 40% v/v ethanol, and presented mild coffee flavor. Several volatile compounds were identified in this distillate among of which, higher alcohols were quantitatively the most abundant group. Isoamyl alcohol (3-methyl-1-butanol), isobutanol (2-methyl-1-propanol), and 2-methyl-1- butanol were the higher alcohols found in major quantities (810, 269, and 185 mg/l, respectively), contributing thus for the greatest proportion of the total aroma and essential character. Ethyl acetate and acetaldehyde, which are also volatile compounds of large influence on the flavor of alcoholic beverages, were found in SCG distillate in concentrations of 38 mg/l and 80 mg/l, respectively. On the other hand, methanol that is a compound harmful to the health was found at low level (11 mg/l). Considering the flavor, the volatile compounds present, and the ratio between isoamyl alcohol/2- methyl-1-propanol and 2-methyl-1-propanol/1-propanol, which are indicative of the quality of alcoholic beverages and have to be higher than unity, it was concluded that a novel spirit of acceptable organoleptic character can be produced by fermentation using SCG as raw material.